2013
DOI: 10.1186/1756-0500-6-188
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of Manuka honey on Clostridium difficile

Abstract: BackgroundManuka honey originates from the manuka tree (Leptospermum scoparium) and its antimicrobial effect has been attributed to a property referred to as Unique Manuka Factor that is absent in other types of honey. Antibacterial activity of Manuka honey has been documented for several bacterial pathogens, however there is no information on Clostridium difficile, an important nosocomial pathogen. In this study we investigated susceptibility of C. difficile to Manuka honey and whether the activity is bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 28 publications
1
30
1
Order By: Relevance
“…In their study, 50% manuka honey solution showed zones of inhibition ranging from 14·2 to 14·5 mm after 2 days of incubation for the three strains of C. difficile which included a reference strain (ATCC 9689) and two clinical isolates of PCR ribotypes 027 and 106. In addition, MIC and MBC values of 6·25% v/v were observed for manuka honey against the three C. difficile isolates, suggesting bactericidal activity (Hammond and Donkor ). In our study, MICs for the WA‐produced manuka honey were more than fourfold higher against the four C. difficile isolates than those obtained in Hammond and Donkor () study and no bactericidal activity was observed at the highest concentration of honey solutions used.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In their study, 50% manuka honey solution showed zones of inhibition ranging from 14·2 to 14·5 mm after 2 days of incubation for the three strains of C. difficile which included a reference strain (ATCC 9689) and two clinical isolates of PCR ribotypes 027 and 106. In addition, MIC and MBC values of 6·25% v/v were observed for manuka honey against the three C. difficile isolates, suggesting bactericidal activity (Hammond and Donkor ). In our study, MICs for the WA‐produced manuka honey were more than fourfold higher against the four C. difficile isolates than those obtained in Hammond and Donkor () study and no bactericidal activity was observed at the highest concentration of honey solutions used.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, MIC and MBC values of 6·25% v/v were observed for manuka honey against the three C. difficile isolates, suggesting bactericidal activity (Hammond and Donkor ). In our study, MICs for the WA‐produced manuka honey were more than fourfold higher against the four C. difficile isolates than those obtained in Hammond and Donkor () study and no bactericidal activity was observed at the highest concentration of honey solutions used. This could be because different strains of C. difficile were used in each study, however, is also likely due to differences between the two honey samples tested, as the activity of honey can vary significantly due to the spatial and temporal variation in sources of nectar (Kwakman et al .…”
Section: Discussionmentioning
confidence: 91%
“…Finally, for the sake of completeness, we examined other commonly measured caecal microbial groups such as Lactobacillus , known to respond to manuka honey (Rosendale et al, 2008); E. coli , known to be inhibited by manuka honey (Lu et al, 2013; Rosendale et al, 2008), and the Clostridium perfringens group (Paturi et al, 2010), representing commensal Gram positive gut microbiota known to be inhibited by manuka honey (Hammond & Donkor, 2013), using RT-qPCR (Paturi et al, 2010) but no significant changes in numbers were evident (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…However, concentrations between 20 and 50% (w/v) Manuka honey resulted in decreasing amount of biofilm formed by all test strains after 24 hours. Although MIC and MBC of Manuka honey against suspensions of the C. difficile strains used in this study were 6.25% (v/v) [21], much higher concentrations of 30-50% (w/v) of Manuka honey were required to deplete biofilms formed by the C. difficile strains.
Figure 2 The effect of varying concentrations of Manuka honey on biofilm of C. difficile strains.
…”
Section: Resultsmentioning
confidence: 99%